Asuhan Keperawatan Gerontik Pada NY. S Dengan Penerapan Rebusan Daun Kumis Kucing Untuk Menurunkan Kadar Asam Urat Di Wilayah Kerja Puskemas Tanjung Buntung Kota Batam Tahun 2020 - Yulia, Revi; Fitri, Rama Yeni Jalia (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
Gout arthritis is a joint disease caused by high levels of uric acid in the blood. High uric acid levels in the blood that exceed the normal limit cause a buildup of uric acid in the joints and other organs with a uric acid level in women is 2.4-6 mg / dl while in men it is 3.5-7.5 mg /dl.(Noviyanti,2015). Based on the Batam city health office, Gout arthritis is in the 6th position of elderly problems, namely 5095 cases and Tanjung Buntung Puskesmas with 145 cases (Batam City Health Office, 2019) This professional scientific paper aims to perform Gerontic Nursing Care for Mrs. S With Cat Whisker Leaf Decoction to Reduce Uric Acid Levels At Tanjung Buntung Health Center In 2020, and held on October 14, 2020 to October 30, 2020. The method used in this Professional Scientific Writing paper is a case study conducted based on the stages of nursing care. includes assessment, diagnosis, intervention, implementation and evaluation of nursing. The results of professional scientific papers obtained 3 nursing diagnoses, namely acute pain associated with biological injury agents (joint swelling), risk of falling related to joint stiffness, and physical mobility barriers related to joint pain. Through the therapy of cat's whiskers leaf decoction, it is hoped that it can become one of the non-pharmacological treatments to reduce uric acid levels in gouty arthritis patients.